A Young Male with Severe Myocarditis and Skeletal Muscle Myositis. (14th June 2018) - Ibrahim, Abdalla; Meagher, Eoghan; Fraser, Alexander; Kiernan, Thomas J.
Abstract : A 34-year-old male presented with retrosternal chest pain, fatigue, shortness of breath, and a history of a previous episode of myocarditis four years prior. He had elevated troponin T, normal skeletal muscle enzymes, and negative inflammatory markers. Cardiac magnetic resonance imaging (MRI) confirmed active myocarditis with extensive myocardial fibrosis and normal left ventricular ejection fraction (LVEF). His myocarditis symptoms resolved with steroids and anti-inflammatory treatment, but on closer questioning, he reported a vague history of long-standing calf discomfort associated with episodes of stiffness, fatigue, and flu-like symptoms. MRI of the lower legs consequently demonstrated active myositis in the calf muscles. Immunomodulatory therapy was commenced with good effect. The patient is undergoing regular follow-up in both cardiology and rheumatology outpatient departments. Repeated MRI of the legs showed significant interval improvement in his skeletal muscle myositis, and repeat cardiac MRI demonstrated the resolution of myocarditis along with persistent stable extensive myocardial fibrosis and preserved LVEF. The patient has returned to full-time work.